Methodological approaches in Kurdish studies theoretical and practical insights from the field - Baser, Bahar (Kurdish societies, politics, and international relations, 2018)
This book sheds light on the intricacies of conducting fieldwork on highly politicized and sensitive topics as well as in conflict settings. It addresses both the epistemological and theoretical along with the practical challenges related to such fieldwork in Kurdish Studies.